Digital elevation models: Where do we go from here? (Journal on Geoinformatics, Nepal, 2003)
This papers examines the current status of DEM generation and discusses current research which may lead to better quality DEMs. Data from so many different sensors can now be used for DEM generation that it is necessary to set out their advantages and disadvantages. There are also many applications of DEMs, and ways of processing and presenting them, and new research is constantly extending and improving these. Some of these methods are discussed and these include improved stereomatching, better representation of the surface and the use of data fusion.